2019
DOI: 10.1097/sla.0000000000002561
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive versus Open Distal Pancreatectomy for Ductal Adenocarcinoma (DIPLOMA)

Abstract: Comparable survival was seen after MIDP and ODP for PDAC, but the opposing differences in R0 resection rate, resection of Gerota's fascia, and lymph node retrieval strengthen the need for a randomized trial to confirm the oncological safety of MIDP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(88 citation statements)
references
References 34 publications
6
69
0
Order By: Relevance
“…Although there was no statistically significant difference, the lower mean number of harvested lymph nodes during MIPD compared with OPD may invite criticism that MIPD is not suitable for oncological pancreatic surgery, even when assuming that the extent of MIPD is similar to OPD. This result is similar to the result about PSM study of minimal invasive distal pancreatectomy for PDAC that the number of harvest LN and positive LN is less than that of open distal pancreatectomy [13]. However, Tomlinson et al [42] reported that examination of 15 lymph nodes is optimal for the accurate staging of PDAC after PD.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Although there was no statistically significant difference, the lower mean number of harvested lymph nodes during MIPD compared with OPD may invite criticism that MIPD is not suitable for oncological pancreatic surgery, even when assuming that the extent of MIPD is similar to OPD. This result is similar to the result about PSM study of minimal invasive distal pancreatectomy for PDAC that the number of harvest LN and positive LN is less than that of open distal pancreatectomy [13]. However, Tomlinson et al [42] reported that examination of 15 lymph nodes is optimal for the accurate staging of PDAC after PD.…”
Section: Discussionsupporting
confidence: 84%
“…However, PSM analysis alone is not sufficient to confirm that there is no difference in survival between MIPD and OPD due to pathological differences between groups, such as perineural invasion. Differences in pathology were also found in PSM study of minimal invasive distal pancreatectomy for PDAC [13]. Because of these limitations, this study attempted to determine whether the surgical procedure affected survival regardless of pathology outcomes using a multivariate Cox proportional hazard model for patients selected by PSM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, minimally invasive distal pancreatectomy (MIDP) has progressed since the introduction of robotic pancreatectomy [4]. Several systematic reviews with meta-analysis and cohort studies also showed that MIDP, including both laparoscopic and robotic, distal pancreatectomy, had better or comparable perioperative outcomes than open distal pancreatectomy (ODP) [5][6][7]. Furthermore, we also conducted a nation-wide multicenter comparative study between MIDP and ODP with more than ORIGINAL ARTICLE 2,000 patients using propensity score-matching and showed that MIDP was associated with more favorable outcomes than ODP [8].…”
Section: Introductionmentioning
confidence: 99%
“…(n = 37, 14.7%) was associated with prolonged overall survival [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]) versus 20 months (95% CI [15][16][17][18][19][20][21][22][23][24], P = 0.049], as compared with upfront resection. Conclusion.…”
mentioning
confidence: 99%